PERKAWINAN SIRRI DALAM PERSPEKTIF HUKUM DI INDONESIA - Supriyadi Supriyadi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
The phenomenon of sirri marriage occurs in many communities, as if the community is permissive to the marriage. They believe that the marriage of sirri is legal according to local law and does not contradict the ethical value of society. This certainly requires a deep legal examination so as not to become a wrong view by the community. Therefore, in this paper, a juridical normative approach is used to analyze sirri farming. The results show that the marriage of Sirri is an illegitimate marriage in the perspective of Marriage Law No. 1 of 1974. Marriage sirri does not have an authentic deed, so someone who makes a marriage sirri will find it difficult to prove the occurrence of marriage.